A simple contagion process describes spreading of traffic jams in urban networks - Meead Saberi (Nature Portfolio, 2020)
Predicting and controlling traffic congestion propagation is an ongoing challenge in most urban settings. Here, Seberi et al. apply a contagion model describing epidemic spread in population to model traffic jams, and verify its validity using large-scale data from six different cities around the world.